A Mini-Review on the Phytochemistry and Pharmacology of the Plant Carica Papaya L. (Caricaceae) - Clement Inkoto Liyongo; Colette Masengo Ashande; Clarisse Falanga Mawi; Blaise Membo wa Mbembo; Jean-Jacques Amogu Domondo; Mahendra Ilmi S Matondang; Jean-Pierre Kayembe Kayembe; Pius Tshimankinda Mpiana; Koto-te-Nyiwa Ngbolua (Britain International for Academic Research (BIAR) Publisher, 2020)
Medicinal plant is an important element of indigenous medical systems all over the world. The ethno botany provides a rich resource for natural drug research and development. Carica papaya is used in Traditional Medicine since a long time. Our investigations started by a search of relevant literature on the plant species. Databases such as Science direct, PubMed, Google Scholar and Scopus were used successively to retrieve the articles on C. papaya. The chemical structures of isolates compounds from this plant were drawn using ChemBioDraw Ultra 12.0 software package. Finally, bibliographical references were made using bibliographical software